KETERAMPILAN PENGELOLAAN KELAS GURU TK DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Risma, Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this study was to determine the skills of classroom management of a kindergarten teacher in kelurahan Simpang Baru kecamatan Tampan kotaPekanbaru. This is a descriptive study, the data was collected using a questionnaire-shaped instrument number 29 point statement. Once tested, the questionnaire is valid for 23 items and is not valid for 6 items. Overall a reliable instrument to "count r" = 0.953 means very high reliability. The population in this study was a kindergarten teacher in kelurahan  Simpang Baru kecamatan Tampan kota Pekanbaru with number 74. Samples are 42 teachers. Results of research data shows that overall classroom management skills by kindergarten class teacher in kelurahan Simpang Baru kecamatan Tampan kota Pekanbaru city excellent condition with a percentage of 84.61%, because it is in the range of 81% -100%. That is a skill teachers to create a conducive learning, skills teacher control in the event of disruption in the learning and skills in managing classroom teachers need to be retained and that needs to be improved to make it better again. Keywords: Classroom Management